Hubungan Gaya Kepemimpinan Transformasional Kepala Sekolah dan Budaya Organisasi Sekolah Dengan Kepuasan Kerja Guru SD di Kecamatan Cidahu - Nurhadidjah, Ani; Ervin Reliavirli Rusti; Hidayat, Zainur (Journal of Contemporary Issue in Elementary Education, 2023)
This study aims to determine the relationship between the principal's transformational leadership style, organizational culture, and job satisfaction of state elementary school teachers in Cidahu District, Sukabumi Regency. The research design used is descriptive research with a correlational approach. Subjects in this study (N = 163) were taken from the population and became a saturated sample. Data analysis used product moment correlation and multiple linear regression analysis with the help of SPSS v23 for Windows. The research results show that: (1) There is a positive and significant relationship between the transformational leadership style of school principals and teacher job satisfaction, with a correlation value of 0.694. (2) Based on a statistical study using the Pearson correlation test, there is a positive and significant relationship between school organizational culture and teacher job satisfaction with a correlation value of 0.620. (3) The results of multiple regression tests show that the relationship between the transformational leadership style variable of the school principal (X1) and school organizational culture (X2) simultaneously has an impact on teacher job satisfaction (Y), which is equal to 54%.